2012
DOI: 10.1002/stem.1193
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A Isozymes are Markers of Human Melanoma Stem Cells and Potential Therapeutic Targets

Abstract: Although the concept of cancer stem cells (CSCs) is well accepted for many tumors, the existence of such cells in human melanoma has been the subject of debate. In the present study, we demonstrate the existence of human melanoma cells that fulfill the criteria for CSCs (self-renewal and differentiation) by serially xenotransplanting cells into NOD/SCID mice. These cells possess high aldehyde dehydrogenase (ALDH) activity with ALDH1A1 and ALDH1A3 being the predominant ALDH isozymes. ALDH-positive melanoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
265
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(292 citation statements)
references
References 53 publications
16
265
0
1
Order By: Relevance
“…ALDH (aldehyde dehydrogenase) activity, often measured via ALDEFLUOR assay, has been successfully used as a marker to enrich CSC populations 11,[17][18][19][20][21][22] in a variety of cancers including human melanoma 23 and head and neck squamous cell cancer. 18 We characterized CSC-enriched populations in 2 histologically distinct murine tumors (melanoma D5 and squamous cell cancer SCC7) and evaluated their immunogenicity by administering CSC-based vaccines in 2 genetically different syngeneic immunocompetent hosts followed by tumor challenge.…”
Section: Introductionmentioning
confidence: 99%
“…ALDH (aldehyde dehydrogenase) activity, often measured via ALDEFLUOR assay, has been successfully used as a marker to enrich CSC populations 11,[17][18][19][20][21][22] in a variety of cancers including human melanoma 23 and head and neck squamous cell cancer. 18 We characterized CSC-enriched populations in 2 histologically distinct murine tumors (melanoma D5 and squamous cell cancer SCC7) and evaluated their immunogenicity by administering CSC-based vaccines in 2 genetically different syngeneic immunocompetent hosts followed by tumor challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Later, other groups developed a convenient method to measure intracellular ALDH1 activity in live cells (7,9). To date, this method is widely used to isolate HSCs from blood and CSCs from many tumor types, including leukemia (5,8,9), breast cancer (6), melanoma (10), lung cancer (11), and others (12,13). Ginestier et al found that ALDH1 is a good marker for malignant human mammary stem cells and that high-ALDH1 activity cell populations leads to substantial tumorigenesis, poor prognosis, and increased metastasis in xenografted mouse models (6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, above therapy following surgical resection of primary tumor inhibited recurrence of the disease and extended survival of mice. Luo et al 21 have shown that ALDH1A isoenzymes are markers of human MSC as well. Moreover, they demonstrated that ALDH1-positive melanoma cells are more tumorigenic and more resistant to chemotherapeutics in mice models.…”
Section: Discussionmentioning
confidence: 99%